PENINGKATAN MOTIVASI BELAJAR SISWA MATERI SISTEM PERNAPASAN PADA TUBUH MANUSIA MELALUI MODEL PROBLEM BASED LEARNING DI KELAS V SD GMIT KUANINO 3 KOTA KUPANG - Ndun, Minenci Sulayana; Bani, Marsi; Kota, Martha K (Journal of Character and ELementary Education, 2024)
The purpose of this study was to increase students' learning motivation on the material of the respiratory system in the human body through a problem-based learning model in class V of GMIT Kuanino 3 Elementary School in Kupang city. This research is a classroom action research (PTK) conducted in two cycles, namely: planning, implementation, observation, and reflection. The subjects of this research were the fifth-grade students of GMIT Kuanino 3 elementary school in Kupang city which amounted to 20 people. The data collection techniques used were observation and learning motivation tests. The data analysis techniques used is descriptive quantitative and qualitative. cycle (I) the results of teacher activity analysis reached 61.11%, student activity analysis at 45.83%, and student learning motivation questionnaire 40%. In cycle (2) teacher activity analysis 93.05%, student activity analysis 81.25% student learning motivation questionnaire 95% The results of this study indicate that the use of problem-based learning (PBL) model can increase the learning motivation of fifth-grade students of SD GMIT Kuanino 3 kupang city.